Understanding ontogenetic trajectories of indirect defence: ecological and anatomical constraints in the production of extrafloral nectaries - Villamil, Nora (Oxford University Press, 2013)
BACKGROUND AND AIMS: Early ontogenetic stages of myrmecophytic plants are infrequently associated with ants, probably due to constraints on the production of rewards. This study reports for the first time the anatomical and histological limitations constraining the production of extrafloral nectar in young plants, and the implications that the absence of protective ants imposes for plants early during their ontogeny are discussed. METHODS: Juvenile, pre-reproductive and reproductive plants of Turnera velutina were selected in a natural population and their extrafloral nectaries (EFNs) per leaf were quantified. The anatomical and morphological changes in EFNs during plant ontogeny were studied using scanning electron and light microscopy. Extrafloral nectar volume and sugar concentration were determined as well as the number of patrolling ants. KEY RESULTS: Juvenile plants were unable to secrete or contain nectar. Pre-reproductive plants secreted and contained nectar drops, but the highest production was achieved at the reproductive stage when the gland is fully cup-shaped and the secretory epidermis duplicates. No ants were observed in juvenile plants, and reproductive individuals received greater ant patrolling than pre-reproductive individuals. The issue of the mechanism of extrafloral nectar release in T. velutina was solved given that we found an anatomical, transcuticular pore that forms a channel-like structure and allows nectar to flow outward from the gland. CONCLUSIONS: Juvenile stages had no ant protection against herbivores probably due to resource limitation but also due to anatomical constraints. The results are consistent with the growth-differentiation balance hypothesis. As plants age, they increase in size and have larger nutrient-acquiring, photosynthetic and storage capacity, so they are able to invest in defence via specialized organs, such as EFNs. Hence, the more vulnerable juvenile stage should rely on other defensive strategies to reduce the negative impacts of herbivory.